Interest-Free Banking - Uzair, Mohammad (Karachi : Royal Book Co., 1978)
The book starts with a brief introduction, discussing the framework of Islamic economics and the capital therein. There are other chapters on Central banking and Strategy for practical introduction of interest-free banking.
Includes bibliographical references and index.
osc 22/5/17
Loans
Keywords: Banks and banking; Interest; Islam